2015
DOI: 10.1002/acr.22412
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Medical Costs of Knee Osteoarthritis Management in the United States: Impact of Extending Indications for Total Knee Arthroplasty

Abstract: Objective The impact of increasing utilization of total knee arthroplasty (TKA) on lifetime costs in persons with knee OA is under-studied. Methods We used the Osteoarthritis Policy Model to estimate total lifetime costs and TKA utilization under a range of TKA eligibility criteria among US persons with symptomatic knee OA. Current TKA utilization was estimated from the Multicenter Osteoarthritis Study and calibrated to Health Care Utilization Project (HCUP) data. OA treatment efficacy and toxicity were draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
296
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 317 publications
(302 citation statements)
references
References 58 publications
4
296
0
2
Order By: Relevance
“…4 For example, 9.3 million people in the United States have symptomatic knee OA, and the average discounted lifetime costs for people with a diagnosis of knee OA are estimated at $140,300. 5 Despite the high prevalence and the significant economic burden, OA of the knee remains incurable. 6,7 The main problem with OA of the knee, and the biggest factor in the disability of patients, is pain.…”
Section: Introductionmentioning
confidence: 99%
“…4 For example, 9.3 million people in the United States have symptomatic knee OA, and the average discounted lifetime costs for people with a diagnosis of knee OA are estimated at $140,300. 5 Despite the high prevalence and the significant economic burden, OA of the knee remains incurable. 6,7 The main problem with OA of the knee, and the biggest factor in the disability of patients, is pain.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this group have suggested that COMP may be used as a potential biomarker to diagnose OA patients, suggesting also the possibility to establish cutoff serum COMP levels to discriminate between the grades of severity of disease. 2 Our study aimed to measure and compare serum and SF COMP levels in patients with primary KOA and healthy individuals to find out whether COMP could have a potential role for diagnosis in KOA patients. Moreover, we aimed to compare SF and serum levels of this biomarker considering age, sex, severity of disease and diurnal variation.…”
Section: Discussionmentioning
confidence: 99%
“…2 In Mexico, the prevalence of OA is estimated at 14% and it has been considered as the fourth cause of morbidity in adults over 60 years of age. 3 Knee osteoarthritis involves cartilage degradation, joint space narrowing, osteophyte formation at the joint margins, and subchondral changes.…”
mentioning
confidence: 99%
“…Jeff Katz presented the socio-economic relevance of total knee replacement (TKR) 43 . Dr. Katz explained that an increasing trend in TKR utilization can be due to increasing incidence and prevalence of knee OA, expanding indications to younger and less functionally disabled patients, growing availability of orthopedic hardware, and changing patient preferences.…”
Section: Risk Factors and Structural Outcomesmentioning
confidence: 99%